STABILITY OF NONLINEAR NABLA FRACTIONAL DIFFERENCE EQUATIONS USING FIXED POINT THEOREMS - Jagan Mohan, J.; Shobanadevi, N.; Deekshitulu, G.V.S.R. (Italian Journal of Pure and Applied Mathematics, 2014)
Difference equations are often used to analyze sampled data systems, in which stability problems are considered to be important. This is evident from a large number of research papers dedicated to it. However, stability results for nonlinear nabla fractional difference equations are not yet reported. The present article discusses stability of nonlinear nabla fractional difference equations of Riemann–Liouville and Caputo type, using fixed point theory.